Uncovering the burden of intentional injuries among children and adolescents in the emergency department. Issue 2 (December 2015) - Khan, Uzma; Hisam, Butool; Zia, Nukhba; Mir, Muhammad; Alonge, Olakunle; Jamali, Seemin; Hyder, Adnan; Razzak, Junaid
Abstract Introduction In low- and middle-income countries, injuries are a leading cause of mortality in children. Much work has been done in the context of unintentional injuries but there is limited knowledge about intentional injuries among children. The objective of this paper was to understand the characteristics of children with intentional injuries presenting to emergency departments in Pakistan. Methods The data was from the Pakistan National Emergency Departments Surveillance (Pak-NEDS), conducted from November 2010 to March 2011 in seven major emergency departments of Pakistan. Data on 30, 937 children under 18 years of age was collected. This paper reports frequency of intentional injuries and compares patient demographics, nature of injury, and discharge outcome for two categories of intentional injuries: assault and self-inflicted injuries. Results Intentional injuries presenting to the emergency departments (EDs) accounted for 8.2% (2551/30, 937) amongst all other causes for under 18 years. The boy to girl ratio was 1:0.35. Intentional injuries included assault (n = 1679, 65.8%) and self-inflicted injuries (n = 872, 34.2%). Soft tissue injuries were most commonly seen in assault injuries in boys and girls but fractures were more common in self-inflicted injuries in both genders. Conclusion Intentional injury is one of the reasons for seeking emergency treatment amongst children and a contributor to morbidity in EDs of Pakistan. Moreover, such injuries may be underestimated due to lack of reporting and investigative resources. Early identification may be the first step leading to prevention.